Consumer intentions to purchase on foreign multi-sided digital platforms: A context of the COVID-19 pandemic - Marzanna Katarzyna Witek-Hajduk; Anna Grudecka (International Journal of Management and Economics, 2022)
Objectives: To explore the determinants of consumer purchase intentions on foreign multi-sided e-commerce platforms (MSPs) within the context of the COVID-19 pandemic. Methods applied: The study relies on a survey of a representative sample of 810 Poles. Partial least squares structural equation modeling (PLS-SEM) was applied to analyze the data. Findings: The study confirms the influence of the perceived usefulness and legal protection of online purchases, changes in retailers' activity during the pandemic, and perceived value of purchases on a MSP on purchase intentions. Originality/value: The article provides insight into consumer online behavior, i.e., determinants of the intention to purchase via MSPs, including those not extensively studied yet. It also takes into account the context of the COVID-19 pandemic. This study's results may be valuable both from the prism of its contribution to the literature on consumer behavior and to business practitioners.
Keywords: M39; 650; COVID-19 pandemic; cross-border commerce; determinants of online shopping; multi-sided digital platforms